2012
DOI: 10.1039/c2cc31316b
|View full text |Cite
|
Sign up to set email alerts
|

Stepping towards highly flexible aptamers: enzymatic recognition studies of unlocked nucleic acid nucleotides

Abstract: Enzymatic recognition of unlocked nucleic acid (UNA) nucleotides was successfully accomplished. Therminator DNA polymerase was found to be an efficient enzyme in primer extension reactions. Polymerase chain reaction (PCR) amplification of a 81 mer UNA-modified DNA library was efficiently achieved by KOD DNA polymerase.Development of nucleic acid therapeutics has attracted significant interest for the treatment of many diseases. With one aptamerbased drug, Macugen (Pegaptanib sodium), 1 on the market for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Locked nucleic acids (LNAs) contain a ribofuranose ring in a locked, single conformation leading to duplex stabilization (Vester and Wengel, 2004). Alternatively, “unlocked” nucleic acids (UNAs) synthesized by Therminator DNA Polymerase offer additional substrate functionalization (Dubois et al, 2012). Other examples of functionalized DNAs made by Therminator DNA Polymerase using modified nucleotides include 2′-fluoro-NTPs (Kasuya et al, 2014), glyceronucleotides (gNTPs) (Chen et al, 2009), 7′,5′-Bicyclo-NTPs (Diafa et al, 2017), 3-phosphono-L-Ala-dNMPs (Yang and Herdewijn, 2011; Giraut et al, 2012), 3′-2′-phosphonomethyl-threosyl-NTPs (Renders et al, 2007, 2008), 5′-3′-phosphonomethyl-dNTPs (Renders et al, 2007, 2008), 2′-deoxy-2′-isonucleoside (iNTPs) (Ogino et al, 2010), 3′-deoxyapionucleotide 3′-triphosphates (apioNTPs) (Kataoka et al, 2008, 2011), 5-trifluoromethyl-dUTP (Holzberger and Marx, 2009) and 4′-C-aminomethyl-2′-O-methyl-TTP (Nawale et al, 2012).…”
Section: Synthesis Of Modified Functional Polymers and Aptamers Usingmentioning
confidence: 99%
“…Locked nucleic acids (LNAs) contain a ribofuranose ring in a locked, single conformation leading to duplex stabilization (Vester and Wengel, 2004). Alternatively, “unlocked” nucleic acids (UNAs) synthesized by Therminator DNA Polymerase offer additional substrate functionalization (Dubois et al, 2012). Other examples of functionalized DNAs made by Therminator DNA Polymerase using modified nucleotides include 2′-fluoro-NTPs (Kasuya et al, 2014), glyceronucleotides (gNTPs) (Chen et al, 2009), 7′,5′-Bicyclo-NTPs (Diafa et al, 2017), 3-phosphono-L-Ala-dNMPs (Yang and Herdewijn, 2011; Giraut et al, 2012), 3′-2′-phosphonomethyl-threosyl-NTPs (Renders et al, 2007, 2008), 5′-3′-phosphonomethyl-dNTPs (Renders et al, 2007, 2008), 2′-deoxy-2′-isonucleoside (iNTPs) (Ogino et al, 2010), 3′-deoxyapionucleotide 3′-triphosphates (apioNTPs) (Kataoka et al, 2008, 2011), 5-trifluoromethyl-dUTP (Holzberger and Marx, 2009) and 4′-C-aminomethyl-2′-O-methyl-TTP (Nawale et al, 2012).…”
Section: Synthesis Of Modified Functional Polymers and Aptamers Usingmentioning
confidence: 99%
“…Since this method affords much longer sequences from readily available natural DNA templates, if successful, it would be a versatile method for use in a variety of applications. Therefore, intense efforts are currently underway toward efficient enzymatic synthesis of modified ONs by using not only primer extension and PCR amplification using DNA polymerases but also in vitro transcription with RNA polymerases. A typical example of this research area is the investigation of the evolution of aptamers. To the best of our knowledge, there are very few examples in which PCR proceeds in the presence of all four kinds of chemically modified dNTPs instead of natural dNTPs. Andreola et al reported PCR in the presence of all four kinds of α-phosphorothioate dNTPs (α-PS-dNTPs); however, the incorporation efficiency of the full length product was very low .…”
mentioning
confidence: 99%
“…9,10 In addition, UNA nucleotides can also be recognised by polymerases, offering great potential in developing novel polymerase-based diagnostic assays involving UNA. 11 Single nucleotide polymorphisms (SNPs) refer to a specic genetic variation occurring in the whole genome, and there are several genetic disorders associated with SNPs. 12 Thus, SNPs detection or mismatch discrimination technology plays a key role in identifying the root cause of such diseases for the appropriate therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“… 9,10 In addition, UNA nucleotides can also be recognised by polymerases, offering great potential in developing novel polymerase-based diagnostic assays involving UNA. 11 …”
Section: Introductionmentioning
confidence: 99%